Implementation of Ergonomic Socio-Culture to Improve Health Quality and Caring Attitude Toward Local Wisdom in Tailoring - Ni Putu Sri Arnita; Anak Agung Ketut Sri Wiraswati; Ni Made Gandhi Sanjiwani; Ni Luh Putu Mia Lestari Devi (International Journal Labs, 2026)
Majejasung is closely related to religious ceremonies in Bali. With the passage of time, the younger generation has become increasingly reluctant to learn tailoring. This is attributed to the prevalence of a consumerist and convenience-driven lifestyle, whereby many choose to purchase ready-made ceremonial attire. The specific objectives of this study were to examine the role of ergonomic socio-culture in improving health quality and fostering caring attitudes toward the local wisdom of sekaa sesung in sekaa teruna. The method employed was experimental, specifically a quasi-experimental research design, using a same-subject design with a randomized posttest-only control group pattern. The targeted findings were: the implementation of ergonomic socio-culture could improve health quality, as evidenced by reductions in boredom and fatigue measured using the Boredom and Fatigue Questionnaire (30-Item Rating Scale), and an increase in caring attitude toward the local wisdom of tailoring, measured using the Caring Attitude toward Local Wisdom Questionnaire. The results demonstrated that the implementation of ergonomic socio-culture improved health quality, as evidenced by: (a) a reduction in boredom by 39.17%; (b) a reduction in fatigue by 33.54%; (c) an increase in caring attitude toward the local wisdom of tailoring by 45.06%. Thus, it can be concluded that ergonomic socio-culture improves health quality (by reducing boredom and fatigue) and enhances caring attitudes toward local wisdom in sekaa teruna.